ANALYZING STUDENTS' INTEREST IN LEARNING ENGLISH IN XIMIA2 GRADE OF SMA MUHAMMADIYAH 8 CERME - Ana Abidin; Lathifah I; Pradita Eka L; Wiwik Wahyuni; Istiqomatul F (Universitas Muhammadiyah Gresik, 2014)
Students’ interest is an essential tool in learning English. Students’ interest could give a positive energy for student direct to learning activities. Thus, the objective of learning activities can be achieved. Students’ interest is also an important factor which affects students’ achievement and learning environment in teaching and learning English as a foreign language. This research conducted at XI-MIA2 grade in SMA Muhammadiyah 8 Cerme. The aim of this study is to analyze students’ interest in learning English. The participants of the study were students in the eleven grades of SMA Muhammadiyah 8 Cerme the academic year of 2013/2014. The number of the students consists of 26 students, 20 persons female and 6 persons male. In this study, the technique that the writer used to collect the data were observation and questionnaire. Based on the data analysis, the writer concluded that students’ interest in learning English at XI-MIA2 was still low. The teacher should make a comfortable environment while teaching and learningEnglish process. Also, using an effective strategy to teach English will increase students’ interest.